Rhodium‐Catalyzed Enantioselective Intramolecular CH Silylation for the Syntheses of Planar‐Chiral Metallocene Siloles1. (23rd April 2015) - Zhang, Qing‐Wei; An, Kun; Liu, Li‐Chuan; Yue, Yuan; He, Wei
Abstract: Reported herein is the rhodium‐catalyzed enantioselective CH bond silylation of the cyclopentadiene rings in Fe and Ru metallocenes. Thus, in the presence of ( S )‐TMS‐Segphos, the reactions took place under very mild conditions to afford metallocene‐fused siloles in good to excellent yields and with ee values of up to 97 %. During this study it was observed that the steric hindrance of chiral ligands had a profound influence on the reactivity and enantioselectivity of the reaction, and might hold the key to accomplishing conventionally challenging asymmetric CH silylations.